The effect of exercise on depressive symptoms in adolescents: a systematic review and meta-analysis - Carter, Tim; Morres, Ioannis; Meade, Oonagh; Callaghan, Patrick (Elsiever, 2016)
Objective: The purpose of this review was to examine the treatment effect of physical exercise on depressive symptoms for adolescents aged 13 to 17 years.